Work Organization, Wage Pressure in the Secondary Labor Market, and the Green Card - Josef Falkinger; Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2001)
Two trends have marked the politico-economic discussion in many industrialized countries in recent years. On the one hand, international production, workplace decentralization, shareholder orientation and generous manager remuneration have changed the face of firms in the primary economy. On the other hand, there is increased pressure on the secondary labor market revealed by unemployment or declining wages of low-skilled workers. This paper establishes a causal relationship between the two trends by developing a model in which labor market segmentation stems from the fact that organizational labor (management) is a key element in the primary, but not in the secondary economy. We also evaluate the effectiveness of selective immigration policies for high-skilled workers (green card).
Keywords: 330; Dual labor market; reorganization of work; organizational labor; international competition; green card